PERBEDAAN FAAL PARU ANTARA PEROKOK TEMBAKAU DENGAN PEROKOK ELEKTRIK DI KOMUNITAS PAKAM REGION VAPORIZER - IWAN DWI JATMIKO; SRI REZEKI ARBANINGSIH (JURNAL ILMIAH KOHESI, 2021)
Lung function can be disrupted due to frequent exposure to substances from outside the body, one of which is exposure tocigarette smoke. This study aims to determine the differences in lung function of tobacco smokers with electric smokers,carried out in the Pakam Region Vaporizer community in street Diponegoro Pasar 1 Lubuk Pakam, Kede Kopi Poda.This study uses cross-sectional research, the source of data obtained from primary data obtained directly from two groups ofsmokers by means of measurement using spirometry. The sample of this study with a total sampling method of 30 peoplewas divided into 2 parts 15 samples of tobacco smokers and 15 samples of electric smokers. This study shows that there isa significant difference between the lung smokers' physiology and those of electric smokers, that is p = 0,000 (p <0.05)obtained by Tobacco Smokers, moderate obstructive results of 2 people (6.7%), and heavy obstructive of 1 person (3 , 3%)while the medium mixture was 4 people (13.3%) and the heavy mixture was 8 people (26.7%) and the moderate smokersobtained moderate obstructive results as much as 2 people (6.7%), while the moderate mixture results were 13 people(43.3%) out of a total of 15 samples of tobacco smokers and 15 sambels of electric smokers, there are a total of 30 samplesin total. There is a difference between the lung capacity of tobacco smokers and electric smoker.